Forced sterilization and the perception of human rights violations among law students in Puno, Peru - Chui Betancur, Heber Nehemias; Pérez Argollo , Katia; Yucra Quispe , Teofilo; Achata Cortez, Cesar Augusto; Jinez García, Esther Lidia; Quispe Clavijo, Esmeralda (REVISTA ELECTRONICA IBEROAMERICANA, 2025)
The World Medical Association has strongly condemned the practice of forced and coerced sterilisation, as a form of violence that causes serious harm to physical and mental health, as well as representing a clear violation of human rights. In this context, the present research aims to identify the perceived factors in the human rights violation of forced sterilisation from the perspective of law students at the Universidad Privada San Carlos (UPSC) in Puno, Peru. This study, with an explanatory design, involved 110 law students, 46.4% of whom were female and 53.6% were male. The results of the multiple linear regression analysis revealed that restrictions to the application of medical ethics (β = 0.498; P<0.01), restrictions to the right to autonomy (β = 0.308; P<0.05) and restrictions to the guarantee of public health (β = 0.150; P<0.001) were the predictors of human rights violations due to forced sterilisation. The findings of this analysis have important implications for policy-making and medical practice.